Melt electro-written scaffolds with box-architecture support orthogonally oriented collagen. (30th December 2021) - Bosworth, Lucy A; Lanaro, Matthew; O'Loughlin, Danielle A; D'Sa, Raechelle A; Woodruff, Maria A; Williams, Rachel L
Abstract: Melt electro-writing (MEW) is a state-of-the-art technique that supports fabrication of 3D, precisely controlled and reproducible fiber structures. A standard MEW scaffold design is a box-structure, where a repeat layer of 90° boxes is produced from a single fiber. In 3D form (i.e. multiple layers), this structure has the potential to mimic orthogonal arrangements of collagen, as observed in the corneal stroma. In this study, we determined the response of human primary corneal stromal cells and their deposited fibrillar collagen (detected using a CNA35 probe) following six weeks in vitro culture on these box-structures made from poly( ϵ -caprolactone) (PCL). Comparison was also made to glass substrates (topography-free) and electrospun PCL fibers (aligned topography). Cell orientation and collagen deposition were non-uniform on glass substrates. Electrospun scaffolds supported an excellent parallel arrangement of cells and deposited collagen to the underlying architecture of aligned fibers, but there was no evidence of bidirectional collagen. In contrast, MEW scaffolds encouraged the formation of a dense, interconnected cellular network and deposited fibrillar collagen layers with a distinct orthogonal-arrangement. Collagen fibrils were particularly dominant through the middle layers of the MEW scaffolds' total thickness and closer examination revealed these fibrils to be concentrated within the pores' central regions. With the demand for donor corneas far exceeding the supply—leaving many with visual impairment—the application of MEW as a potential technique to recreate the corneal stroma with spontaneous, bidirectional collagen organization warrants further study.